Kebijakan pendidikan pada era reformasi terhadap sistem pendidikan di Indonesia - Ayna Ayu Farikha; Sri Minarti (Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine educational policies during the Reform Era and their impact on the education system in Indonesia. The research employed a descriptive qualitative approach using library research and interviews. The data were obtained from scientific journal articles and interviews with relevant informants. Data collection techniques were carried out by identifying, collecting, and reviewing sources related to educational policies during the Reform Era. Data analysis was conducted descriptively and qualitatively through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the Reform Era brought significant changes to the education system in Indonesia, particularly through educational decentralization policies, curriculum reforms, improvement of teacher quality, and the implementation of school-based management. Curriculum changes from the Competency-Based Curriculum (KBK), School-Based Curriculum (KTSP), Curriculum 2013, to the Merdeka Curriculum demonstrate the government’s efforts to improve the quality of education in accordance with the development of the times and students’ needs. However, the implementation of educational policies still faces several challenges, such as disparities in educational quality between regions and limitations in educational resources.